Factors Related to The Incidence of Hypertension in The Elderly in The Coastal Area of Bintuhan Health Center Working Area, Kaur Regency - Septinawati Septinawati; Fikitri Marya Sari; Julius Habibi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Intoduction: Hypertension is one of the non-communicable diseases whose prevalence continues to rise in Indonesia, including in Kaur Regency. Lifestyle factors such as unhealthy eating patterns, lack of physical activity, and obesity are suspected to significantly contribute to the incidence of hypertension. This study aims to determine the relationship between dietary patterns, physical activity, and obesity with the incidence of hypertension in the community within the working area of Bintuhan Health Center, Kaur Regency. Method: This research uses a quantitative approach with a cross-sectional design. A sample of 96 respondents was taken through simple random sampling. Data were collected via questionnaires and blood pressure measurements, and analyzed using chi-square tests. Result and Discussion: The analysis results show a significant relationship between dietary patterns (p = 0.001), physical activity (p = 0.005), and obesity (p = 0.000) with the incidence of hypertension. Poor dietary patterns, low physical activity, and obesity status are associated with an increased risk of hypertension. Community-based promotional and preventive interventions need to be enhanced to reduce the burden of hypertension in the area. Conclusion: The health center is expected to strengthen education on healthy eating and lifestyle management for the elderly through a local cultural approach. Regular physical activity programs, such as elderly exercise classes, should be promoted, accompanied by regular monitoring of blood pressure and Body Mass Index (BMI). These preventive and promotional efforts are essential for the sustainable prevention and control of hypertension in coastal communities.